2012
DOI: 10.1007/s11104-012-1520-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil erosion, runoff and nutrient losses in an avocado (Persea americana Mill) hillside orchard under different groundcover management systems

Abstract: Aims Assess the influence of different groundcover management systems on erosion and runoff processes associated with extremely steep hillside avocado (Persea americana Mill) orchards, in a Mediterranean climate with high rainfall variability. Methods We compared several groundcover management systems at a steep hillside avocado planting in a three-year study: 1) Bare soil (BS), pre-and postemergence herbicides; 2) Vegetation strip (VS), postemergence herbicide applied in a 1-m wide strip on the tree row plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 52 publications
6
40
0
2
Order By: Relevance
“…The vegetation coverage influence on erosion rate was also studied by ATUCHA et al (2013) who observed that the vegetation with ryegrass in avocado orchards minimized the erosion in 99.96%, as well as other environmental impacts, reducing nutrient losses by runoff in 79.7% for N and in 94.1% for P, comparing to the bare soil. In this research, the reductions in losses of P were in order of 66.7% with SC of 100% in relation to the bare soil.…”
Section: Interrill Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vegetation coverage influence on erosion rate was also studied by ATUCHA et al (2013) who observed that the vegetation with ryegrass in avocado orchards minimized the erosion in 99.96%, as well as other environmental impacts, reducing nutrient losses by runoff in 79.7% for N and in 94.1% for P, comparing to the bare soil. In this research, the reductions in losses of P were in order of 66.7% with SC of 100% in relation to the bare soil.…”
Section: Interrill Erosionmentioning
confidence: 99%
“…Agríc., Jaboticabal, v.36, n.6, p.1063-1072, nov./dez. 20161064 The impacts caused by erosion can be minimized by using alternative soil cultivation systems (ATUCHA et al, 2013), among them the use of conservation systems that keep the waste on the surface and no soil preparation (TRUMAN et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…High erosion rates have been observed in avocado (Atucha et al, 2013) and olive orchards (Gómez et al, 2003;Vanwalleghem et al, 2010), new citrus plantations (Cerdà et al, 2009b;Li et al, 2015) and vineyards (Novara et al, 2013;Tarolli et al, 2015). Almond (Faulkner, 1995), persimmon , and apricot (Abrisqueta et al, 2007) orchards have also shown high erosion rates, but little research has been carried out comparing agriculture land management in fruit orchards.…”
Section: Introductionmentioning
confidence: 99%
“…/jwld-2016 by MOŢOC et al [1975], IONIŢĂ et al [2006], MIRCEA et al [2010;, MAETENS et al [2012]; hydrological: PETRESCU [1974], STANCIU [2002], YU et al [1997], BENAVIDES-SOLORIO, MACDONALD [ , JOEL et al [2002; forestry by ABAGIU et al [1973], HARTANTO et al [2003]; biological factors [WAIN-WRIGHT et al 2000]; ecologic by GBUREK and SHAR-PLEY [1998], DEBANO [2000], COVINO et al [2010], ATUCHA et al [2013].…”
Section: Introductionmentioning
confidence: 99%